Enhanced NK-92 Cytotoxicity by CRISPR Genome Engineering Using Cas9 Ribonucleoproteins - Huang, Rih-Sheng; Shih, Hsin-An; Lai, Min-Chi; Chang, Yao-Jen; Lin, Steven (Frontiers in Immunology, 2020)
Natural killer (NK) cells are an attractive cell-type for adoptive immunotherapy, but challenges in preparation of therapeutic primary NK cells restrict patient accessibility to NK cell immunotherapy. NK-92 is a well-characterized human NK cell line that has demonstrated promising anti-cancer activities in clinical trials. Unlimited proliferation of NK-92 cells provides a consistent supply of cells for the administration and development of NK cell immunotherapy. However, the clinical efficacy of NK-92 cells has not reached its full potential due to reduced immune functions as compared to primary NK cells. Improvements of NK-92 functions cu¬rrently rely on conventional transgene delivery by mRNA, plasmid and viral vector with limited efficiencies. To enable precise genetic modifications, we have established a robust CRISPR genome engineering platform for NK-92 based on the nucleofection of Cas9 ribonucleoprotein. To demonstrate the versatility of the platform, we have performed cell-based screening of Cas9 guide RNA, multiplex gene knockout of activating and inhibitory receptors, knock-in of a fluorescent gene, and promoter insertion to reactivate endogenous CD16 and DNAM-1. The CRISPR-engineered NK-92 demonstrated markedly enhanced cytotoxicity and could mediate antibody-dependent cellular cytotoxicity against hard to kill cancer cell lines. Our genome editing platform is straightforward and robust for both functional studies and therapeutic engineering of NK-92 cells.